2014
DOI: 10.1371/journal.pone.0095727
|View full text |Cite
|
Sign up to set email alerts
|

Specific Duplication and Dorsoventrally Asymmetric Expression Patterns of Cycloidea-Like Genes in Zygomorphic Species of Ranunculaceae

Abstract: Floral bilateral symmetry (zygomorphy) has evolved several times independently in angiosperms from radially symmetrical (actinomorphic) ancestral states. Homologs of the Antirrhinum majus Cycloidea gene (Cyc) have been shown to control floral symmetry in diverse groups in core eudicots. In the basal eudicot family Ranunculaceae, there is a single evolutionary transition from actinomorphy to zygomorphy in the stem lineage of the tribe Delphinieae. We characterized Cyc homologs in 18 genera of Ranunculaceae, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 62 publications
3
48
0
Order By: Relevance
“…Many additional studies have analyzed the role of CYC2 genes in other rosids and asterids (e.g., Gesneriaceae, Fabaceae, Brassicaceae, Dipsacales). in basal eudicot species with bilaterally symmetrical flowers (e.g., Consolida regalis, ranunculaceae and Capnoides sempervirens, papaveraceae), CYC2 gene expression is also asymmetric (Damerval et al, 2007;Jabbour et al, 2014), which is consistent with a role for these genes in determining the zygomorphy of their flowers. Functional studies also support the implication of these genes in the control of dorsal petal shape (Feng et al, 2006;Busch and Zachgo, 2007;Wang et al, 2008;Wang et al, 2010;Xu et al, 2013, reviewed in Hileman, 2014aand Hileman, 2014b.…”
Section: Cyc2 Genes Control Floral Zygomorphy In Dicotssupporting
confidence: 55%
“…Many additional studies have analyzed the role of CYC2 genes in other rosids and asterids (e.g., Gesneriaceae, Fabaceae, Brassicaceae, Dipsacales). in basal eudicot species with bilaterally symmetrical flowers (e.g., Consolida regalis, ranunculaceae and Capnoides sempervirens, papaveraceae), CYC2 gene expression is also asymmetric (Damerval et al, 2007;Jabbour et al, 2014), which is consistent with a role for these genes in determining the zygomorphy of their flowers. Functional studies also support the implication of these genes in the control of dorsal petal shape (Feng et al, 2006;Busch and Zachgo, 2007;Wang et al, 2008;Wang et al, 2010;Xu et al, 2013, reviewed in Hileman, 2014aand Hileman, 2014b.…”
Section: Cyc2 Genes Control Floral Zygomorphy In Dicotssupporting
confidence: 55%
“…Three independent transitions from polysymmetry to monosymmetry have occurred in Ranunculales: one each in the families Ranunculaceae, Papaveraceae and Menispermaceae (Damerval & Nadot, ). In Delphinieae, characterized by zygomorphic flowers, there is an additional duplication of CYL genes in each of two Ranunculaceae paralog lineages (Jabbour et al ., ). Jabbour et al .…”
Section: Discussionmentioning
confidence: 97%
“…In E. californica, silencing of EscaCYL2 decreased stamen number and, in C. vesicaria , stamen number was also reduced in association with the shift to actinomorphy. Stamen expression of CYL paralogs has also been shown, for example, in Nigella damascena , a representative of the Ranunculaceae family (Jabbour et al ., ). In C. vesicaria , the loss of lateral stamens within the bundles was in concordance with Ronse De Craene & Smets (), who stated that the four stamens of the outer whorl are always the last to be affected by reductions in the androecium.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in the expression pattern of CYC ‐like genes were found to be mainly correlated with cis‐regulatory changes (Busch & Zachgo, ; Yang et al, ). Cis‐regulatory changes in the CYC locus arose multiple times in both eudicots (Luo et al, ; Feng et al, ; Busch & Zachgo, ; Damerval et al, ; Wang et al, ; Jabbour et al, ) and monocots (Bartlett & Specht, ; Preston & Hileman, ) and were crucial in the evolution of zygomorphy in many angiosperm lineages (e.g., Oleaceae and Tetrachondraceae, Zhong & Kellogg, ). Using electrophoretic mobility shift assay and chromatin immunoprecipitation, Yang et al () revealed a double positive auto‐regulatory feedback loop between CYC1C and CYC1D in Primulina heterotricha .…”
Section: Introductionmentioning
confidence: 99%